The Role of Nitric Oxide in Nitrogen Fixation by Legumes - Signorelli, Santiago; Sainz, Martha; Tabares-da Rosa, Sofía; Monza, Jorge (Frontiers in Plant Science, 2020)
The legume-rhizobia symbiosis is an important process in agriculture because it allows the biological nitrogen fixation (BNF) which contributes to increasing the levels of nitrogen in the soil. Nitric oxide (⋅NO) is a small free radical molecule having diverse signaling roles in plants. Here we present and discuss evidence showing the role of ⋅NO during different stages of the legume-rhizobia interaction such as recognition, infection, nodule development, and nodule senescence. Although the mechanisms by which ⋅NO modulates this interaction are not fully understood, we discuss potential mechanisms including its interaction with cytokinin, auxin, and abscisic acid signaling pathways. In matures nodules, a more active metabolism of ⋅NO has been reported and both the plant and rhizobia participate in ⋅NO production and scavenging. Although ⋅NO has been shown to induce the expression of genes coding for NITROGENASE, controlling the levels of ⋅NO in mature nodules seems to be crucial as ⋅NO was shown to be a potent inhibitor of NITROGENASE activity, to induce nodule senescence, and reduce nitrogen assimilation. In this sense, LEGHEMOGLOBINS (Lbs) were shown to play an important role in the scavenging of ⋅NO and reactive nitrogen species (RNS), potentially more relevant in senescent nodules. Even though ⋅NO can reduce NITROGENASE activity, most reports have linked ⋅NO to positive effects on BNF. This can relate mainly to the regulation of the spatiotemporal distribution of ⋅NO which favors some effects over others. Another plausible explanation for this observation is that the negative effect of ⋅NO requires its direct interaction with NITROGENASE, whereas the positive effect of ⋅NO is related to its signaling function, which results in an amplifier effect. In the near future, it would be interesting to explore the role of environmental stress-induced ⋅NO in BNF.